2012
DOI: 10.5194/acp-12-7059-2012
|View full text |Cite
|
Sign up to set email alerts
|

French airborne lidar measurements for Eyjafjallajökull ash plume survey

Abstract: Abstract. An Ultra-Violet Rayleigh-Mie lidar has been integrated aboard the French research aircraft Falcon20 in order to monitor the ash plume emitted by the Eyjafjallajökul volcano in April-May 2010. Three operational flights were carried out on 21 April, 12 and 16 May 2010 inside French, Spanish and British air spaces, respectively. The original purpose of the flights was to provide the French civil aviation authorities with objective information on the presence and location of the ash plume. The present pa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
85
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(88 citation statements)
references
References 34 publications
3
85
0
Order By: Relevance
“…The sun-photometer-derived column-integrated BER of the aerosols can be computed at 440 nm from the single scattering albedo and the backscatter phase function derived from the operational algorithm of AERONET (Dubovik and King, 2000). The root mean square error (RMSE in grey area) on the lidar-derived BER, determined as the variabil-ity over 20 min, is close to 0.004 sr −1 on average, which is comparable with the one retrieved by Chazette et al (2012b) with a similar lidar system set-up in Minorca in the 2012 autumn season. We note a good coherence with the BER at 440 nm derived by the AERONET sun photometer.…”
Section: Aerosol Optical Properties Derived From the Ground-based Lidsupporting
confidence: 48%
See 1 more Smart Citation
“…The sun-photometer-derived column-integrated BER of the aerosols can be computed at 440 nm from the single scattering albedo and the backscatter phase function derived from the operational algorithm of AERONET (Dubovik and King, 2000). The root mean square error (RMSE in grey area) on the lidar-derived BER, determined as the variabil-ity over 20 min, is close to 0.004 sr −1 on average, which is comparable with the one retrieved by Chazette et al (2012b) with a similar lidar system set-up in Minorca in the 2012 autumn season. We note a good coherence with the BER at 440 nm derived by the AERONET sun photometer.…”
Section: Aerosol Optical Properties Derived From the Ground-based Lidsupporting
confidence: 48%
“…PDR is an effective parameter to separate the contribution of the more spherical particles from the ones due to dust-like aerosols (e.g. Chazette et al, 2012b). Between 16 and 19 June the PDR value is between 10 and 27 %, which is representative of non-spherical dust-like aerosols (Müller et al, 2007;Tesche et al, 2011) as identified in Fig.…”
Section: Aerosol Optical Properties Derived From the Ground-based Lidmentioning
confidence: 99%
“…The Falcon 20 aircraft was equipped with an airborne lidar LNG (Pelon et al, 2002) All the lidars can record also the depolarization ratio between the signal polarized parallel and perpendicular to the plane of the outgoing beam. For the ground-based lidar, the uncertainty on the aerosol depolarization ratio is of the order of 1-2 % as explained in Chazette et al (2012). For the airborne lidar LNG, the depolarization ratio is measured at 355 nm and it is calibrated on molecular scattering using a value of 1.5 ± 0.3 % for clean air, corresponding also to 1-2 % error on the aerosol depolarization ratio.…”
Section: The 2013 Mediterranean Lidar Observation Networkmentioning
confidence: 99%
“…Several tests carried on other days earlier during the campaign showed that the gain ratio varied by 5 % at most, so that the value obtained from the Lake Baikal experiment was used during the whole campaign. The PDR is then computed as in Chazette et al (2012). As the PDR is a physical parameter without meaning when there are few aerosols, its calculation is performed only for layers where the aerosol backscatter coefficient is at least 5 % of the molecular backscatter (i.e.…”
Section: Retrieval Of the Pdrmentioning
confidence: 99%
“…The volumetric depolarization ratio (VDR) was determined following the procedure described in Chazette et al (2012). It uses the transmission and reflection coefficients of the polarization separation plates as measured in the lab before departure, along with the gain ratio between the total and perpendicular polarization channels.…”
Section: Retrieval Of the Pdrmentioning
confidence: 99%